Simultaneous Detection of Multiple Surface Acoustic Wave Sensor-Tags for Water Quality Monitoring utilizing Cellular Code-Reuse Approach - Suresh, K. (Institute of Electrical and Electronics Engineers Inc., 2021)
A water quality monitoring application often requires the deployment of Internet of Things (IoT) sensors over a wide water body with communication links among them to transmit, receive the data, and then uplink it to the cloud for further analytics. Deployment of this kind requires battery-assisted IoT sensors which require monitoring the battery level and replacement when necessary. It is thus desirable to have battery-free sensor-tags and a suitable communication infrastructure to obtain data. In this paper, a system that facilitates obtaining sensed data, like pH, through passive sensor-tags based on Surface Acoustic Wave (SAW) technology and a cellular code-reuse scheme based reader infrastructure is proposed. The reader in each cell is able to read multiple sensor-tags simultaneously, which itself has been a challenge. The SAW sensor tags are appropriately proposed to be designed to be orthogonal to allow simultaneous detection and the cell range of reader-SAW sensor-tags communication is sought to be further enhanced through a resonant loading of Interdigital Transducer (IDT) based reflectors. IEEE